A visual description of the convective flow field around the head of a human - Özcan, O; Meyer, KE; Melikov, AK (SPRINGER, 2005)
Mean velocity data obtained by PIV (Particle Image Velocimetry) around the head of a real-life size breathing thermal manikin are presented for two cases of 'no breathing' and continuous exhalation through nose'. Experiments were conducted in a special chamber which provided stationary convective flows around the seated manikin. Results are limited to the plane of symmetry. The paper aims to describe the physical structure of the turbulent flow field by presenting velocity and vorticity data in color graphics.
Keywords: PIV; turbulence; free and forced convection; streamline topology; Computer Science; Imaging Science & Photographic Technology